K30 Lega Italiana Ricerca Huntington's e malattie correlate (LIRH) foundation onlus: promoting research, with care. (13th September 2016) - D'Alessio, Barbara; Maffi, Sabrina; Benvenuti, Arianna; Migliore, Simone; Marano, Massimo; Squitieri, Ferdinando
Abstract : Background: LIRH Foundation is a not for profit organisation whose mission is to conduct and support research on Huntington's disease (HD), providing patients with free of charge assistance, promoting awareness raising initiatives, training professionals and spreading research results. LIRH Foundation has outpatient services for HD in Northern, Middle and Southern Italy. Specific aim: To encourage patients not to stay hidden but to seek for proper assistance by, at the same time, contributing to research progress. Methods: A systematic, clear, easily accessible and scientifically validated communication and information activity conducted by press release, website, webmarketing campaigns, conferences, video, interviews, social networks, brochure, newsletter, networking. Results: Incoming calls to our Toll-Free Number 800.388.330: 3.783 incoming calls in 2015 (20% increase vs 2014). 1.400 incoming calls in the first quarter of 2016. Website: 11.577 users (average) in the first quarter of 2016 vs 3.456 in the same period of 2015; 27.295 page views (average) in the first quarter of 2016 vs 13.135 same period 2015. Assisted HD subjects: Jul 2015-Jun 2016: 590 visits, including 72 first visits vs Jul 2014 – Jun 2016: 250 visits, including 25 first visits Conclusions: Quality and consistency of disclosed information are recognised by patients, who feel encouraged to approach our organisation and to participate in experimental trials (i.e Enroll-HD, Legato-HD and Open PRIDE-HD).